Domestic Violence among Ever Married Women of Reproductive Age Group in a Rural Area of Karnataka: A Cross Sectional Study - Radha Ramaiah; Srividya Jayarama (National Journal of Community Medicine, 2017)
Background: Domestic violence is a widespread social evil and continues to be a major public health problem. Domestic violence by marital partners is the most common type of violence against women. This not only has serious impact on their physical, mental health but also impedes women’s socio-economic development.